Transformações no espaço agrário do sertão do Pajeú: a participação das mulheres no processo de transição agroecológico em quintais de (re)produção da vida - Rapozo, Bruna Maria da Silva (2017)
In the peasant agriculture in the region of Sertão do Pajeú, state of Pernambuco, the women participate of the production of foods, election and cares with the seeds, improvement, handling of biodiversity, commercialization and generation of income of the family. The women farmers are also the sole responsible for the domestic work and for the family's welfare and quality of life. In addition, many women put into practice the traditional knowledge passed on by other women practices healthy relationships compatible with more equitable gender relations. Thus, this work aims to understand how the process of agroecological transition, under way in the region's agroecological yards, modifies the sertanejo agrarian space and social relations. For this analysis, eight agroecological yards of women and men that sell their production in the Ecological Fair of Serra Talhada (Feira Ecológica de Serra Talhada) were selected. The yards selected are located in three municipalities: Santa Cruz da Baixa Verde, Triunfo and Serra Talhada. The results show that for the peasant women, the yards are spaces for life, for the reproduction of the peasant lifestyle and as an experimental laboratory for the construction and refinement of knowledges about the agroecosystems, as well as a place to plant, harvest and live in the semi-arid Sertão. These spaces were devalued as productive spaces by being considered feminine ones, an extension of the domestic space. However, they have been acquiring since the 1990s new values, shapes and practices in the life and in the economy of those women and their families. In this work, we identified that the women who participated in the Ecological Fair of Serra Talhada associated agroecological and traditional knowledges with feminist practices. This fact permits them to construct and reconstruct ideas and values, to problematize and question genre-based social relations, and the importance of women's workforce for their communities and family. Methodologically, we opted for the proceedings of a qualitative research through literature and documentary research as well as field research in the peasant families that collaborated for this study.